FAKTOR- FAKTOR YANG MEMPENGARUHI PERMINTAAN DAN PENAWARAN EKSPOR IKAN HIAS INJEL NAPOLEON POMACANTHUS XANTHOMETAPON DI SULAWESI SELATAN - Kasmi, Mauli (Journal Galung Tropika, 2014)
Indonesian ornamental fish export growth between 1987 to 2010 are likely to continue to rise. According AKKII and AKIS (2008), data obtained from the International Trade Center (ITC) shows the average growth of import demand for the country to reach 15% per year. Destination country or the world ornamental fish market, among others the European Union, the USA, Japan, Singapore and Taiwan. The purpose of the study was to determine the factors that affect the demand and supply of ornamental fish exports injel napoleon and to determine the level of supply and demand injel napoleon fish and its relation to the level of utilization. The analysis used is multiple linear regression models of log-log / double logarithmic models or also called constant elasticity using descriptive method. The data in this study based on the dimension of time, namely the time-series data (time series) derived from primary and secondary data from company exporters ornamental fish and ornamental fish business associations. Ornamental fish export price injel napoleon significant negative effect on the demand for ornamental fish export injel napoleon. Ornamental fish export price injel pajamas significant positive effect on the demand for ornamental fish export injel napoleon. The rupiah exchange rate against the dollar has no significant effect terhada p number injel napoleon fish export demand. Ornamental fish export price injel injel napoleon and pajamas as well as the exchange rate against the dollar significantly influence the number of ornamental fish export demand injel napoleon. Napoleon injel supply curve curved reverse (backward bending supply curve) shows that the supply is declining despite rising prices for suspected fish stock decreases.